Inferior mesenteric artery diameter and number of patent lumbar arteries as factors associated with significant type 2 endoleak after infrarenal endovascular aneurysm repair. (15th April 2022) - Kondov, Stoyan; Dimov, Aleksandar; Beyersdorf, Friedhelm; Maruschke, Lars; Pooth, Jan-Steffen; Kreibich, Maximilian; Kaier, Klaus; Siepe, Matthias; Czerny, Martin; Rylski, Bartosz
Abstract: OBJECTIVES: Our goal was to identify the inferior mesenteric artery diameter and number of patent lumbar arteries causing a significant type 2 endoleak to develop after infrarenal endovascular aneurysm repair. MATERIAL AND METHODS: Included were patients who underwent infrarenal endovascular aneurysm repair between April 2002 and January 2017. Patients with an aneurysm involving the iliac arteries were excluded. Significant type 2 endoleak was defined as a type 2 endoleak observed after infrarenal endovascular aneurysm repair and accompanied by abdominal aneurysm growth of at least 5 mm during that time. RESULTS: A total of 277 patients were included. Mean follow-up was 38.9 (standard deviation 121.6) months. Immediately after infrarenal endovascular aneurysm repair, type 2 endoleaks occurred in 55 patients (20%), resolving spontaneously in 2 patients 6 months after infrarenal endovascular aneurysm repair. Thirty (10.8%) patients revealed a significant type 2 endoleak with aneurysm sack enlargement > 5 mm during follow-up, for which inferior mesenteric artery or lumbar artery coiling was performed. Mean time for coiling after primary infrarenal endovascular aneurysm repair was 25.4 (standard deviation 19.10) months. Twenty-three patients (8.3%) showed a non-significant type 2 endoleak during follow-up (no aneurysm sack enlargement). We found that the inferior mesenteric artery diameter and number of patent lumbar arteries were factors associated with a significant type 2 endoleak (odds ratio 1.755, P = 0.001; odds ratio 1.717, P < 0.001, respectively). Prior to endovascular aneurysm repair, the inferior mesenteric artery was patent in 212 (76.5%) patients; its median diameter measured 3 (0.5–3.8) mm. The median number of patent lumbar arteries was 3 (2–4). According to our receiver operating characteristic curve analysis, an inferior mesenteric artery diameter ≥3 mm (sensitivity 93.3%, specificity 65%) and ≥3 patent lumbar arteries (sensitivity 87.5%, specificity 43.6%) proved to be optimal cut-off values related to developing a significant type 2 endoleak. We therefore propose a composite score for the development of a significant type 2 endoleak [(inferior mesenteric artery diameter + patent lumbar arteries)/2]. CONCLUSIONS: Patients in whom the diameter of the inferior mesenteric artery is ≥ 3 mm and with ≥ 3 patent lumbar arteries carry a higher risk of developing significant type 2 endoleak after infrarenal endovascular aneurysm repair. Abstract : The goal of endovascular aortic repair (EVAR) is to exclude the aneurysm.